2023
DOI: 10.3390/fishes8110544
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Genetic Structure among Four Selected Strains of Whiteleg Shrimp (Litopenaeus vannamei) Using SSR Markers

Zhe Zhang,
Chengkuan Lu,
Kebing Lin
et al.

Abstract: The whiteleg shrimp (Litopenaeus vannamei) is one of the most economically important aquaculture species in China. Genetic diversity is crucial for maintaining the gene pool of farmed shrimp. In this study, the effects of artificial selection on the genetic structure of four whiteleg shrimp strains were evaluated using microsatellite sequences. The results showed that the observed heterozygosity (Ho), expected heterozygosity (He), and the polymorphism information content (PIC) of the four selected strains rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Microsatellite markers are simple sequence repeats of highly polymorphic and codominant DNA motifs (n could range from 8 to 50) that are widely distributed throughout the genomes of eukaryotes and are widely used for different population genetic studies in many different species, such as genetic diversity [ 27 , 28 , 29 ], population structure, parentage determination [ 30 , 31 , 32 ], and constructing genetic linkage maps [ 33 , 34 , 35 , 36 , 37 ], animal identification, meat traceability [ 38 , 39 ] and animal breeding [ 40 , 41 ]. Studies on related aquatic species with highly duplicated genomes have demonstrated that microsatellites derived from transcriptomes are significantly more effective than those developed from the genome using traditional methods [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellite markers are simple sequence repeats of highly polymorphic and codominant DNA motifs (n could range from 8 to 50) that are widely distributed throughout the genomes of eukaryotes and are widely used for different population genetic studies in many different species, such as genetic diversity [ 27 , 28 , 29 ], population structure, parentage determination [ 30 , 31 , 32 ], and constructing genetic linkage maps [ 33 , 34 , 35 , 36 , 37 ], animal identification, meat traceability [ 38 , 39 ] and animal breeding [ 40 , 41 ]. Studies on related aquatic species with highly duplicated genomes have demonstrated that microsatellites derived from transcriptomes are significantly more effective than those developed from the genome using traditional methods [ 42 ].…”
Section: Introductionmentioning
confidence: 99%